Is the Acknowledgment of Earned Entitlement Effect Robust Across Experimental Modes and Populations? - Barr, Abigail; Miller, Luis; Ubeda, Paloma (Sociological methods & research, 2023)
We present a set of studies the objective of which was to test the robustness of the acknowledgment of earned entitlement effect across different experimental modes and populations. We present three sets of results. The first is derived from a between-subject analysis of two independent, but comparable samples of nonstudent adults. One sample participated in a standard, behavioral laboratory experiment and the other participated in a survey experiment. The two methods returned similar treatment effects. The second set of results relates to a sample of students drawn from a behavioral laboratory’s pool of registered subjects. They participated in both the behavioral lab and survey experiments. We perform a between-subject comparison of the two treatment-elicitation methods but, this time, focusing on the same sample of subjects. Again, the treatment effects are very similar. Finally, we establish that within-subjects there is some consistency between decisions made under the two methods.